Biomaterials for Enhancing Neuronal Repair - Cangellaris, Olivia V.; Gillette, Martha U. (Frontiers in Materials, 2018)
As they differentiate from neuroblasts, nascent neurons become highly polarized and elongate. Neurons extend and elaborate fine and fragile cellular extensions that form circuits enabling long-distance communication and signal integration within the body. While other organ systems are developing, projections of differentiating neurons find paths to distant targets. Subsequent post-developmental neuronal damage is catastrophic because the cues for reinnervation are no longer active. Advances in biomaterials are enabling fabrication of micro-environments that encourage neuronal regrowth and restoration of function by recreating these developmental cues. This mini-review considers new materials that employ topographical, chemical, electrical, and/or mechanical cues for use in neuronal repair. Manipulating and integrating these elements in different combinations will generate new technologies to enhance neural repair.